Nursing care for patient in postoperatory heart surgery in the Intensive Care Unit - Ariele Priebe Reisdorfer; Sandra Maria Cezar Leal; Joel Rolim Mancia (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To investigate the critical nodes related to nursing care for patients in the postoperative period of cardiac surgery. Methods: Exploratory study with a qualitative approach. Data collected through semi-structured interviews with 27 members of the nursing team working in the Intensive Care Unit. Material submitted to thematic analysis. Results: Three categories emerged: Flaws in the professional qualification for patient care in the postoperative period of cardiac surgery; Team challenges concerning specific patient care in the postoperative period of cardiac surgery; and (dis) organization of work in the Intensive Care Unit and its impact on nursing care for patients in the postoperative period of cardiac surgery. Final considerations: Given the identification of the critical nodes, the professionals presented suggestions to overcome daily difficulties: investments in strategies for Permanent Education in Health; creation of tools to guide patient assistance in the postoperative of cardiac surgery; and provision of adequate human resources.